Study protocol: A systematic review and meta-analysis regarding the influence of coagulopathy and immune activation on new onset atrial fibrillation in patients with sepsis. - Michael Downes; Ingeborg D Welters; Brian W Johnston (PLoS ONE)
Background New onset atrial fibrillation (NOAF) is the most common arrhythmia affecting critically ill patients with sepsis. NOAF is associated with increased intensive care unit mortality, increased hospital mortality, development of heart failure and increased risk of permanent atrial fibrillation and thromboembolic events such as stroke. The pathophysiology of NOAF has been outlined, however, a knowledge gap exists regarding the association between abnormalities in coagulation and immune biomarkers, and the risk of developing NOAF in patients with sepsis. Methods and analysis This protocol describes a systematic review and meta-analysis following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guideline (PRISMA-P) and the Meta-Analyses and Systematic Reviews of Observational Studies guideline (MOOSE). We will conduct the literature search in Medline, Scopus and Cochrane Library. We will include studies that report data in adult patients (>18 years) with sepsis that develop NOAF. We will extract data from studies that report at least one coagulation or immune biomarker. Risk of bias will be assessed by using the Newcastle Ottawa Scale (NOS) and Risk of Bias 2 tool (RoB2) for non-randomized and randomized trials respectively. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach will be utilized in assessing the quality of evidence. Discussion This systematic review and meta-analysis will explore the scientific literature regarding the association between coagulation and immune activation in critically ill patients with sepsis, who develop NOAF. The findings will add to the existing knowledge base of NOAF in sepsis, highlight areas of uncertainty and identify future areas of interest to guide and improve management strategies for NOAF. Trial registration Registration details. CRD42022385225 (PROSPERO).